2015
DOI: 10.3733/ca.v069n01p36
|View full text |Cite
|
Sign up to set email alerts
|

Post-fire vegetation dynamics of a sagebrush steppe community change significantly over time

Abstract: Sagebrush steppe ecosystems of the Intermountain West have experienced a decline over the past 150 years due to changing fire regimes, invasive species and conifer encroachment. Prescribed fire is a common and cost-effective tool used in sagebrush restoration and fuels management. We examined the post-fire succession of a sagebrush steppe community over a nearly 30-year period at two study sites in northeastern California. The long-term nature of this study was particularly significant, as invasive annual gras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 14 publications
8
17
0
Order By: Relevance
“…Many areas are still susceptible to initial cheatgrass invasion and densification (Miller et al 2011); however, we show a slight downward trend in annual herbaceous cover, possibly due to the fact that 50-60% of the historic sagebrush steppe range either possessed an understory of exotic annual grass (i.e., cheatgrass) or has already been converted to an annual grassland (West 2000). Unburned area differences are consistent with ecological expectations, in that shrub and sagebrush cover is increasing, driven largely by secondary succession (Hanna and Fulgham 2015), while decreases in the study area overall are mostly driven by burns , Shi et al 2018, due to the slow recovery of sagebrush (Baker 2011, Bukowski andBaker 2013). Moreover, when looking at only burned areas, annual herbaceous cover increased at a rate of 0.03% per decade, as expected in burned areas (Hanna and Fulgham 2015).…”
Section: Temporal Trendssupporting
confidence: 83%
See 2 more Smart Citations
“…Many areas are still susceptible to initial cheatgrass invasion and densification (Miller et al 2011); however, we show a slight downward trend in annual herbaceous cover, possibly due to the fact that 50-60% of the historic sagebrush steppe range either possessed an understory of exotic annual grass (i.e., cheatgrass) or has already been converted to an annual grassland (West 2000). Unburned area differences are consistent with ecological expectations, in that shrub and sagebrush cover is increasing, driven largely by secondary succession (Hanna and Fulgham 2015), while decreases in the study area overall are mostly driven by burns , Shi et al 2018, due to the slow recovery of sagebrush (Baker 2011, Bukowski andBaker 2013). Moreover, when looking at only burned areas, annual herbaceous cover increased at a rate of 0.03% per decade, as expected in burned areas (Hanna and Fulgham 2015).…”
Section: Temporal Trendssupporting
confidence: 83%
“…While Shi et al (2018) reported little trend in litter cover, we report a significant decrease of À0.02% per decade. Moreover, when looking at only burned areas, annual herbaceous cover increased at a rate of 0.03% per decade, as expected in burned areas (Hanna and Fulgham 2015). Indeed, reported that most significant trends in cheatgrass performance from 2000 to 2010 in the Northern Great Basin were negative.…”
Section: Temporal Trendsmentioning
confidence: 56%
See 1 more Smart Citation
“…7). The relatively rapid rebound of certain herbaceous functional groups is consistent with work showing that annual and perennial herbaceous species may recover within a few years after burning (Miller et al 2013, Hanna and Fulgham 2015, Shinneman and McIlroy 2016. S2).…”
Section: Fire As a Driver Of Vegetation Changesupporting
confidence: 82%
“…) and should be prevented from burning whenever possible, while higher elevation Mountain big sagebrush ( A. tridentata ssp. vaseyana ) ecosystems may still recover naturally (Hanna and Fulgham ) or with restoration by seeding (Knutson et al. ).…”
Section: Introductionmentioning
confidence: 99%